ENTERPRISE ARCHITECTURE POS (EAPOS) - Rakhmadi Rahman (Pusat Riset dan Inovasi Nasional, 2023)
PT Pos Indonesia (Persero) is a State-Owned Enterprise (BUMN), in 2018 in line with KD72/2018 concerning the Organizational Structure of PT Pos Indonesia (Persero) and KD.35/2018 concerning the Transition Period of Information and Technology Organizations, the IT function organization has smelting is carried out to enter the business unit for the core system, so a guideline is needed for information technology governance or IT management, which is currently decentralized. To be able to standardize the structure and operation of technology support in all overall company functions, including business, data, applications and technology, a simple study is needed in the form of a blueprint or company blueprint which consists of information technology management components so that it can provide an overview and steps steps to assist in formulating EAPOS which bridges business in harmony with IT governance at PT Pos Indonesia (Persero).